(untitled) (Research, Society and Development, 2023)
This article aims to align the benefits of using graphene for civil construction and show possible methods of use in composites, with the purpose of elevating the current construction methods to a new phase of production, malleability, applicability and resistance. Because it is a structure made up of carbon atoms organized in a hexagonal arrangement with a microscopically thin layer, graphene has excellent electrical, thermal, physical-chemical, mechanical and optical properties, giving graphene a huge potential for new technological methods in virtually almost all materials. Graphene has a great capacity to use to improve performance in composites in general, thereby arousing a great interest in the world scientific community in the development of methods for mass production of graphene. In this article, some graphene production techniques were addressed in order to show their technological applications for civil construction based on studies of scientific works, banks of patent documents and research groups registered with the National Council for Scientific and Technological Development (CNPq).